Common Grasshoppers in Florida - J.L. Capinera (EDIS)
This document provides an overview of common grasshopper species in Florida, highlighting their abundance, life cycles, and feeding habits. It introduces researchers and laypeople to various species, such as the Green Slantfaced Grasshopper, Southern Greenstriped Grasshopper, and Southern Lubber Grasshopper. The document also discusses the ecological roles of grasshoppers, their impact on crops and ornamental plants, and their unique behaviors, such as cannibalism and specific plant preferences. Date first printed: January 1992.